Scientific ideas of Floriy Batsevych in dynamics and perspectives of communicative linguistics - Zbinska , Anna (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article is devoted to issues of the formation and prospects of communicative linguistics in the world scientific space. It is noted about its linkswith various professional areas that systematically study communication as a phenomenon, – philosophy, psychology, cultural studies, ethnology, ethnography, sociology, semiotics, communicativistics, rhetoric, cognitology, logic, computer science, theory of artificial intelligence, as well as with all parts of traditional linguistics and the latest linguistic trends, in particular media linguistics, business linguistics, etc.The professional ideas of K. Levi-Strauss, J. Austin, J.L. Searle, P. Strawson, C.-S. Peirce, L. Wittgenstein, K. Shannon, W. Weaver, K. Bühler, W. Schramm, E. Noel-Neumann, H. Lasswell, X. Garfinkel, E. Hoffmann, and others are mentioned. Special research attention is paid to the figure of Professor Floriy Batsevych as the founder of communicative linguistics in Ukrainian science. The role of the scientist in the interdisciplinary dynamics of the direction, the objectivity of which consists in the analysis of the functioning of the language in different communicative situations, solving the issues of effective / ineffective conflict / non-conflict communication, necessarily oriented to the extralinguistic context, is defined. The author's position regarding the non-identity of the concepts "communication" and "communication" is argued.The perspective of constructive dialogue of communicative linguistics and functional stylistics is commented on the example of stylistic analysis of business communication. The communicative nature of business is determined as one of the most dynamic discourses in the social sphere nowadays, which explains its resource and potential, represented as variably as possible in different texts, genres and contexts. This made it possible rationally to explain the presence of business in the mass media, in official, scientific communicative paradigms – in those spheres that systematically determine the priorities of the development of modern society in time and space of culture. And also to determine the prospects of professional analysis of business-relevant communication strategies and tactics, integrally synchronized with the named areas and formulated research problems.
Keywords: communicative linguistics, Floriy Batsevych, communicative strategies and tactics, stylistics of business communication, current research epistemes, business linguistics, media linguistics.